Beaconless Packet Forwarding Approach for Vehicular Urban Environment - Kashif Naseer Qureshi; Abdullah Hanan Abdullah; Fasee Ullah (Bulletin of Electrical Engineering and Informatics, 2016)
Existing wireless technologies provide communication and information services to all fields of life. The one of the emerging and popular field is vehicular ad hoc networks, with its unique characteristics and highly mobile environment. Different types of routing protocols have been proposed to address the routing issues in network and one of the most efficient types is geographical routing. In this type of protocols, the beacon messages are using to update the node locations and positions. However, these protoocls have been suffered with high channel congestion issue in the network. To this end, we propose a beaconless packet forwarding strategy based on modified handshake messages mechanism. The protocol uses some realistic metrics to select the next forwarder node such as forward progresss and link quality. The protocol performance is evaluated with existing beacon and beaconless geographical routing protocols. The simulation results showed the better performance of the proposed protocol in terms of packet delay and data delivery ratio in realistic wireless channel conditions.